(untitled) - Sockman, Ralph Washington; (1889-1970) (U.S.A, 1961)
This study has not been prepared merely for those who are puzzled about the mystery of their own misery. It is written for those who are sufficiently Christian to be concerned about the sufferings of others. This little book is written for three groups of people: those who are in suffering
Keywords: Suffering